Estudio técnico para el tratamiento de aguas ácidas en los drenajes de la industria minera. - Rosas Blas, Rony Peter (2015)
In developing the thesis entitled "Technical Study Water Treatment in the Mining Industry drains" before the treatment itself, knowing the chemical composition of a mineral, we calculated the potential maximum acidity potential. neutralization and net neutralization potential, whose relations allow us to predict whether the mineral explode or produce no acidic water in order to take the appropriate steps and use preventive methods (liabilities), rather than corrective (assets). In the active treatment of mine water it is important to know the chemical analysis of mine water, in order to make the strategy of the case, as the uses that will give the treated water. In this specific case, initially the pH rises to 2.5 to 4 using calcium hydroxide, which allows the iron precipitate. At this stage the iron is removed as iron hydroxide by filtration. Subsequently raising the pH remains between 4 and 7, which allows precipitate et chromium. It followed by raising the pH from 7 to 8.1 wherein the Cu+2 cation precipitates. Finally the pH is raised to 10.5 8.1 to precipitate Zn+2, Ni+2, Pb+2, Cd+2. Once separated most cations in alkaline medium, is required to bring the pH to a neutral value. Paradoxically this is achieved by adding sulfuric acid. Spoils free water of a number of cations which have precipitated as insoluble hydroxides which are jointly with calcium sulfate as solids removed is obtained as a result. A calculation program uses as chemical analysis data and mine water volume that calculates the total mass of calcium hydroxide and the necessary total mass of solids formed is developed.